2012
DOI: 10.1007/s00248-012-0097-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Consortium of Millepora dichotoma Exhibiting Unusual Multifocal Lesion Event in the Gulf of Eilat, Red Sea

Abstract: Colonies of the hydrocoral Millepora dichotoma along the Gulf of Eilat are exhibiting unusual tissue lesions in the form of white spots. The emergence and rapid establishment of these multifocal tissue lesions was the first of its kind reported in this region. A characterization of this morphological anomaly revealed bleached tissues with a significant presence of bacteria in the tissue lesion area. To ascertain possible differences in microbial biota between the lesion area and non-affected tissues, we charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Phylogenetic analysis revealed the genus Kordiimonas to be closely related to the genera Eilatimonas and Temperatibacter (Teramoto & Nishijima, 2014). They can be distinguished from other groups within the class Alphaproteobacteria by their cellular fatty acid composition, having high contents of iso-and anteiso-branched fatty acids (Paramasivam et al, 2013;Teramoto & Nishijima, 2014;Xu et al, 2014). A novel Kordiimonas strain, M41 T , was isolated from a surface seawater sample collected from the western Pacific Ocean and was subjected to taxonomic study using a polyphasic approach.…”
mentioning
confidence: 99%
“…Phylogenetic analysis revealed the genus Kordiimonas to be closely related to the genera Eilatimonas and Temperatibacter (Teramoto & Nishijima, 2014). They can be distinguished from other groups within the class Alphaproteobacteria by their cellular fatty acid composition, having high contents of iso-and anteiso-branched fatty acids (Paramasivam et al, 2013;Teramoto & Nishijima, 2014;Xu et al, 2014). A novel Kordiimonas strain, M41 T , was isolated from a surface seawater sample collected from the western Pacific Ocean and was subjected to taxonomic study using a polyphasic approach.…”
mentioning
confidence: 99%
“…Differences between 2011 and 2012 are significant at 0.5 and 2.5 m (p = 0.016 and p = 0.014, respectively). The difference between 0.5 and 2.5 m depth is significant (p < 0.001) Paramasivam et al (2012) showed that, while the gross morphology of the white spots is characterized by seemingly bleached tissue, the spots underwent some tissue necrosis, release of zooxanthellae, and symbiophagy (e.g. digestion of the zooxanthellae by their host; see Downs et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The DNA G+C content of strain 5-11 T was 44.3 mol%. This value was lower than those for the genera Kordiimonas (50-58 mol%; Yang et al, 2013) and Eilatimonas (60.3 mol%; Paramasivam et al, 2013) and was relatively low for members of the class Alphaproteobacteria (Garrity et al, 2005).…”
mentioning
confidence: 87%
“…Strains: 1, 5-11 T ; 2, K. gwangyangensis GW14-5 T or JCM 12864 T (data from Kwon et al, 2005;Xu et al, 2011;Yang et al, 2013); 3, K. lacus S3-22 T (Xu et al, 2011); 4, K. aestuarii 101-1 T (Math et al, 2012); 5, K. aquimaris MEBiC06554 T (Yang et al, 2013); 6, E. milleporae MD2 T (Paramasivam et al, 2013 …”
Section: (Gu289640)mentioning
confidence: 99%